The impact of inadequate nutrition on children's health (International Seven Journal of Multidisciplinary, 2024)
The increase in childhood obesity in developed countries, such as the US, results from the combination of inadequate diets and low level of physical activity, exacerbated by socioeconomic and environmental factors. Studies show a continuous growth in obesity rates, impacting children's physical and mental health and highlighting the urgent need for effective nutritional interventions and public policies. Nutrition education and access to healthy foods are essential to reverse this trend.